(untitled) (World Bulletin of Social Sciences, 2023)
This article highlights such issues as the competencies noted in the standards of international assessment programs, the analysis of tasks presented in international assessment programs of previous years, the formation of skills for developing course developments based on innovative methods embodied in international assessment programs.